PRESSURE DRIVEN CONDUCTING POLYMER MEMBRANES DERIVED FROM LAYER BY LAYER FORMATION AND CHARACTERIZATION: A REVIEW - IZZATI IZNI YUSOFF; ROSIAH ROHANI; ABDUL WAHAB MOHAMMAD (Journal of Engineering Science and Technology, 2016)
The layer-by-layer method is a technique used for the fabrication of ultra-thin defect free films which involves alternating sequential adsorption of polycations and polyanions, while conducting polymer is characterized by a conjugated structure of alternating single and double bonds. The use of layer-by-layer in producing a membrane for separation has received considerable interest due to its properties. However, the introduction of conducting polymer as a base membrane is relatively new. Therefore, in this review, we discuss in detail three types of LBL techniques (dip, spin and spray layer-by-layer) along with their parameters. We will also summarize current developments on the characterization of modified membrane prepared using the layer-by-layer techniques in terms of morphology, physical and chemical properties, and separation performances.